The health risks associated with the consumption of food supplements without nutritional guidance (Research, Society and Development, 2021)
Supplements are composed of vitamins, minerals and other substances that are formulated to complement the individual's need in case of insufficiency in a traditional diet, to meet the individualized metabolic and physiological conditions. The objective of the present work is to verify the health risks associated with the consumption of food supplement without nutritional guidance. This work is a bibliographic review, where the following databases were accessed: Scielo, Lilacs, Medline and VHL. The total number of articles consulted for the achievement of the objectives proposed in this research, to the integrative review were carried out with 68 articles, the exclusion criteria were applied, being 20 discarded, published from the year 2015 to the year 2021, corresponding to a total of 48 items used at work. The nutritionist is of paramount importance in guiding food supplements for the correct and safe use, as the diet needs to be planned according to the needs of each individual and for the appropriate prescription of nutritional supplements. Thus, nutritionists who work together with people who are developing physical activities are professionals with the necessary training to provide guidance on the use and the real need for dietary supplements for practitioners of physical exercises, thus avoiding harming health with indiscriminate use.